Farm boy : the sequel to War horse - Morpurgo, Michael (Scholastic Press, 2012)
For years Joey was a war horse, pulling ambulance carts and artillery through the battlefields of World War I. Finally he returned to Albert and the farm. Now, decades later, Albert's son loves to tell his own grandson stories about the remarkable horse, including its feats in the war and of the time the family risked everything betting that Joey could win a daring race.